Pengaruh Penempatan terhadap Kinerja Pegawai pada Kantor Kementerian Agama Kota Jambi - Nabilah Fauziyah Hasna (Universitas Batanghari Jambi, 2019)
This research aims to find out how the placement of an employee in Ministry of Religion Office in Jambi City. Next to analyze how to work target in the Ministry of Religion Office in Jambi City. And also to analyze how the influence of placement on performance clerk in Ministry of Religion Office in Jambi City. This research uses descriptive method quantitative correlational research with the form that describes the relationship of the free variables with variables bound. The research on the analysis tools using simple regression with hypothesis prove with statistical tests t. The results showed that the placement of significant effect on performance clerk where marked with a t calculate > t tables and the Prog. SIG α (0.05) <. While the correlation value i.e. 59.8% of these mean that occur close relationships between placement variables with employees performance variables.Keywords: Placement: Employee Performance